Efektivitas Media Video Animasi dalam Meningkatkan Pengetahuan dan Keterampilan Menggosok Gigi pada Siswa TK Keledang Samarinda - Yulia Anindita Prasetianti; Emelia Tonapa; Desies Rahmawati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Dental caries remains a common oral health problem among preschool children due to inadequate knowledge and improper tooth-brushing skills. This study aimed to determine the effectiveness of animated video media in improving tooth-brushing knowledge and skills among students at Keledang Kindergarten, Samarinda. A pre-experimental study with a one-group pretest–posttest design was conducted involving 66 respondents. The variables examined were tooth-brushing knowledge and skills. Knowledge was assessed using a questionnaire, while tooth-brushing skills were evaluated through an observation checklist. Data were analyzed using the Wilcoxon test. The results showed an improvement in the proportion of respondents with good knowledge from 59.1% at pretest to 100% at posttest, while the proportion of respondents categorized as highly skilled increased from 3% to 95.5%. Statistical analysis revealed significant differences in both knowledge and tooth-brushing skills (p = 0.000). Animated video media is effective in improving tooth-brushing knowledge and skills among preschool children and can serve as an alternative strategy for oral health promotion.